Kegiatan Cyber Public Relations Diskominfo Jabar Melalui Instagram @humas_jabar - Ichwan, Galuh Puteri Nurul; Muhtadi, Asep Saeful (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2022)
This This study aims to find out an overview of the stages of cyber public relations activities carried out by the West Java Communication and Informatics Service through social media instagram @humas_jabar. This study uses the model of The Circular Model of SoMe for Social Communication by Regina Luttrell with the paradigm of constructivism through qualitative descriptive methods as well as data collection techniques through in-depth interviews, passive post-participation observations and collected documentation. Researchers describe the stages of managing Instagram social media @humas_jabar starting from sharing, optimizing, managing, and engaging. The results showed that the cyber public relations activities carried out by IKP Diskominfo West Java through Instagram @humas_jabar, through four stages in it, the first stage is disseminating content, the second stage is maximizing messages, the third stage is managing information, and the last stage is involving the public.